Wireless Positioning: Principles and Practice - Sharp, Ian.; Yu, Kegen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on non-GNSS positioning systems and approaches. Although it addresses both theoretical and practical aspects, the primary focus is on engineering practice. This is achieved by providing in-depth studies on a number of major topics such as tracking system architecture, link budget, system design, implementation, testing, and performance evaluation. It studies four positioning application cases in detail: covert vehicle tracking, horse racing, rowing, and tracking for field sports. Its comprehensive and systematic treatment of practical issues in wireless positioning makes the book particularly suitable for readers who are interested in learning about practical wireless positioning solutions. It will also benefit researchers, engineers and graduate students in fields such as positioning and navigation, geospatial engineering and telecommunications.
Introduction -- Part I Engineering of Positioning Systems -- Architecture of tracking systems -- Signaling techniques -- Use of inertial sensors in position determination -- Link budget -- Application cases -- System testing -- Part II Recent Research into Terrestrial Positioning -- Wideband reconstruction based positioning -- Toa error measurement, modeling and analysis -- Gdop analysis for indoor positioning -- Enhanced least-squares positioning algorithm -- Receiver signal strength positioning -- Integrated indoor positioning -- Positional accuracy measurement and error modeling -- Concluding remarks.
Keywords: Telecommunication; Signal processing; Communications Engineering, Networks; Signal, Speech and Image Processing